(untitled) (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted at the Agronomy Field of Patuakhali Science and Technology University, Dumki, Patuakhali from June to December, 2013 to find out the effect of variety and planting density on the yield and yield attributing characters of local aromatic rice. The experiment was laid out in a factorial randomized complete block design with three replications, which consisted of three local aromatic rice varieties (Chinigura, Shakhorkhora and Kalizira) and four planting densities were viz. S1 (25 cm × 20 cm), S2 (20 cm × 20 cm), S3 (20 cm × 15 cm) and S4 (20 cm × 10 cm). The results revealed that the local aromatic rice var. Shakhorkhora variety produced the highest number of grains per panicle (131) and 1000-grain weight (13.8 g), consequently higher grain (2.63 t ha-1), followed by Kalizira (2.56 t ha-1) and straw yield (4.21 t ha-1). One the other hand, higher number of tillers per hill (14.8), number of grains per panicle (140 nos.) were found in 20 cm × 20 cm spacing with higher grain yield. Bangladesh J. Agril. Res. 43(3): 489-497, September 2018